The Implications of E-Commerce on Labor Productivity in the Philippines - Gabinete, Felina Elizabeth; Delos Santos, Kane Rayah; Red, Mig Freedom; Camaro, Peter Jeff (International Journal of Social and Management Studies, 2022)
The relationship between Labor Productivity and independent variables, Technology, and Electronic Commerce was examined in this study. Since the start of E-Commerce in the Philippines, it is known to have positive effects on economy-wide establishments that contribute to the growth of the Philippine economy. Furthermore, it served as an opportunity for undergraduates to pursue jobs and improve the employment capacity of the Philippines. Its dynamic capabilities allow Filipino consumers to browse websites with easier and faster access as compared to the primitive way of purchasing in the commerce industry. After using cross-sectional data and Pearson Correlation Coefficient, this study proved that E-Commerce and technology have an implication on labor productivity.